Musical Improvisation - Pernek, Špela (Širjenje obzorij o poučevanju glasbe, 2025)
The aim of this chapter is to emphasize the importance of musical improvisation for the development of musical skills and creativity in primary school pupils. Through improvisation, children not only expand their rhythmic, melodic, and tonal vocabulary but also stimulate their creativity, express ideas, and build a deeper, more personal connection with music. Additionally, improvisation enables them to convey their feelings and thoughts in a musical form. The chapter highlights the significant role of teachers in introducing musical improvisation, outlining approaches they can use to encourage pupils’ improvisation through diverse activities, such as exploring musical styles and engaging in various projects. It is also essential for teachers to create a supportive and safe environment where students feel confident and motivated to express their ideas.